Morphological and molecular analysis of coconut(cocos nucifera l.) - Selvaraju S (Department of Plant Breeding and Genetics, College of Agriculture, 2008)
The research project entitled Morphological and molecular analyses of coconut (Cocos nucifera L) was carried out in the Department of Plant Breeding and Genetics College of Agriculture, Vellayani during the year 2006-2008.